Alternatives to Using Revenues of Governmental Property Management - Bilousova О. S. (Statistics of Ukraine, 2017)
The article deals with the problems of the target orientation and efficiency of the use of resources received from the management of state-owned objects, which are extremely relevant in the context of budget deficit, growth of expenditures on repayment and servicing of public debt, and the necessity of state support to economic development processes. The purpose of the article is to study the alternative of using revenues from the management of state property and to develop, taking into account the experience of the EU countries, proposals for improving the budget statistics of incomes and expenditures of the State Budget of Ukraine. It was found that over the period of 2012-2016, the total revenues from the management of state-owned objects amounted to UAH 266.7 billion. In 2015-2016 gains from privatization decreased. The total revenue from the management of state-owned objects in 2016 compared to 2015 decreased by UAH 14 billion, and amounted to 64 billion UAH. It has been established that the limited amount of such revenues requires an increase in the level of their use for the purpose of economic development and strengthening of the stimulating influence on investment processes in the country It is concluded that alternatives to using revenues from state property management are the repayment of public debt; financing the creation and implementation of innovations; co-financing with private entities managing the modernization of the real economy sector on an innovative basis. It is proposed to introduce a special account within the budget to distinguish the formation and use of funds received from privatization and other types of management of state-owned objects. In order to improve the fiscal statistics of revenues and expenditures of the State Budget of Ukraine, we consider it expedient to supplement the annual report on budget execution with the application, which will reflect the volume of accumulated in the year of funds in terms of sources of formation, and the amount of expenditures spent on the areas of use in the context of investment projects.